Urban Life and the Ambient in Smart Cities, Learning Cities, and Future Cities - McKenna, H. Patricia, 1954-, author 650202; IGI Global Scientific Publishing (Online service) 655412 (Hershey, Pennsylvania : IGI GLOBAL, 2023)
The topic of urban life and the ambient in smart cities, learning cities, and future cities is a timely one, fitting as it does in the world today by responding in an interdisciplinary way across many areas of research and practice. It is essential for researchers to think about and engage with the notion of flourishing in increasingly challenging environments in smarter ways. Urban Life and the Ambient in Smart Cities, Learning Cities, and Future Cities expands upon explorations of urban life to the ambient. As such, perspectives are offered in this work on urban life in the context of smart cities, learning cities, and future cities, enriched by understandings of the ambient, infusing the interactions of people and technologies in 21st-century environments with increased awareness, at the moment. Covering topics such as ambient learning, smart homes, and extended realities, this premier reference work is an essential resource for students and educators of higher education, architects, urban planners, instructional designers, sociologists, city officials, community leaders, librarians, researchers, and academicians.